DI-058 Risk of drug–drug interactions in a pulmonary arterial hypertension population. (25th February 2017) - Suárez, J Arrojo; Manzaneque, A; Garcia, N Corominas; Creus, M Tuset; Mir, JA Barberà
Abstract : Background: Recent progress in pulmonary arterial hypertension (PAH) research has made possible the expansion of treatment options improving the prognosis of patients. Due to multimorbidity and increasing age, patients are much more likely to be exposed to polypharmacy. As a result, there is an increased risk of drug–drug interactions affecting efficacy as well as the toxicity of the treatment. In 2012, the pulmonary hypertension unit of our hospital was designated as a reference unit by regional health authorities. Purpose: To identify potential drug–drug interactions (PDDIs) between oral drugs (OD) for PAH and medications used to treat concomitant illnesses. Material and methods: A cross sectional study was conducted in April 2016 in a tertiary hospital. All outpatients on OD for PAH with their chronic medication recorded in the regional electronic database were included. We collected demographic data, concomitant pharmacotherapy and PAH treatment. PDDIs were identified using the local Guide of Interactions in Pulmonary Hypertension. Results: 174 patients (224 OD) were included: 63.8% women, mean age 59 years (range 18–91). Most of the OD prescribed were bosentan and sildenafil (both 29%) followed by tadalafil (15.2%), ambrisentan (13.8%), riociguat (8.5%) and macitentan (4.5%). Approximately 30% of the patients received combined oral therapy. Median number of drugs per patient was 9 (range 2–19) and 83.9% were polymedicated (≥ 5 drugs). We identified a total of 237 PDDIs (67% of patients had at least one and over 30% more than two): 83% were moderate and 16% contraindicated according to their possible clinical relevance; 62% were pharmacokinetic and 38% pharmacodynamic; 70% affected the co-medication, 27% the OD and 3% both; 68% resulted in an increase in toxicity, 29% in decreased of efficacy and 3% both. The main contraindicated PDDIs were: beta-blockers with bosentan (n=10) and sildenafil (n=8), and bosentan with immunosuppressants (n=7). Polymedicated patients were more likely to have PDDIs (p<0.05). Conclusion: PDDIs represent a significant issue among patients with PAH. Evaluation of these PDDIs could result in the establishment of a better treatment plan for these patients. However, more prospective studies are required to investigate the clinical relevance of PDDIs and their influence on therapeutic outcomes. References and/or acknowledgements: Ciraci R, et al. Pulm Pharmacol Ther2014;28:1–8. No conflict of interest